In Situ Depositing Ag NPs on PDA/SiW11V Co‐encapsulated Fe3O4@TiO2 Magnetic Microspheres as Highly Efficient and Durable Visible‐light‐driven Photocatalysts. Issue 1 (19th November 2020) - Wu, Panfeng; Xue, Qi; Liu, Jiquan; Wang, Tianyu; Feng, Caiting; Liu, Bin; Hu, Huaiming; Xue, Ganglin
Abstract: The design and preparation of highly efficient and durable visible‐light‐driven photocatalysts remain a great challenge in the environment remediation. In this paper, a new multi‐component composite, Fe3 O4 @TiO2 @PDA/SiW11 V−Ag, is successfully fabricated by in situ assembling Ag nanoparticles (NPs) onto polydopamine (PDA) and mono‐vanadium substituted silicotungstate (SiW11 VO40 6−, simplified as SiW11 V) co‐encapsulated Fe3 O4 @TiO2 magnetic microspheres. In the photodegradation of methyl orange (MO) and photocatalytic reduction of Cr(VI) under visible light, the multi‐component composite displays the enhanced catalytic efficiency in comparison with other catalysts with less‐components. Structure‐reactivity relationship is established based on the correlation between photocatalytic efficiency and transient photocurrent intensity. Notably, the multi‐component composite exhibits high stability and durability in wide range of pH aqueous solutions and most of organic solvents. The successful preparation of this novel type of materials provides a promising approach for constructing stable photocatalysts with multi‐components, where poor compatibility of each component can be well bridged via PDA as an efficient linker and charge transport. Abstract : Photocatalysis : A stable, high photocatalytic activity and recoverable multi‐component composite magnetic catalyst Fe3 O4 @TiO2 @PDA/SiW11 V−Ag was successfully prepared. The catalyst exhibit excellent photocatalytic performance for the removal of MO and photoreduction of Cr(VI) under visible‐light irradiation.